Prescription drug brand Web sites: Guidance where none exists - Lewis Glinert, Ph.D (University of Minnesota Libraries Publishing, 2010)
This paper applies insights from linguistics and discourse analysis to prescription drug brand Web sites, with special reference to the 100 top-selling drugs. Such sites give the outward appearance of being a place to go for straightforward information about a specific brand. In reality, they present a confused mix of brand information, health information and hype, muddled organization, and poor indication of authority, creating an imbalance between benefit and risk content. In so doing, they breach the letter and spirit of the regulations governing direct-to-consumer advertising, which the FDA has by default applied to such Web sites but which were not designed for this special type of discourse. The many communicative difficulties proven to be caused by Web sites in general, in particular for the elderly and less literate, also pose ethical problems. A rethinking of the verbal and visual design of these drug sites is needed -- and new regulatory guidance, for which this paper offers recommendations. At stake is not just the quality of health information at brand drug sites but also their credibility.